2020
DOI: 10.1097/mca.0000000000000931
|View full text |Cite
|
Sign up to set email alerts
|

Colchicine therapy in patients with coronary artery disease: a systematic review and meta-analysis of randomized controlled trials

Abstract: Introduction Inflammation is a substantial mediator of atherosclerosis. Colchicine has anti-inflammatory effects and has been investigated in many randomized controlled trials (RCTs) in patients with coronary artery disease (CAD). Methods We searched PubMed/MEDLINE, Cochrane library, and Embase databases (inception through 28 February 2020) for RCTs evaluating colchicine in CAD patients. The outcomes of interest were major adverse cardiovascular events … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 33 publications
0
11
1
Order By: Relevance
“…Although some recent trials have demonstrated that treatment with colchicine improved outcomes in patients with recent myocardial infarction, and chronic coronary disease, published evidence that treatment with colchicine may be associated with improvements in cardiovascular outcomes has been inconsistent. [20][21][22][23] In FAST, while prophylaxis against flares of gout was offered to all patients, only some accepted it, those who took it mainly did so at the very beginning of the trial, and it is likely that some patients chose to take it for less than the six months provided. It is unlikely that the relatively short-term administration of low dose colchicine or NSAIDs as prophylaxis, or any differences in concomitant use of colchicine or NSAIDs, even with the imbalances between treatment groups, had any major effect on the long-term outcomes of FAST.…”
Section: Discussionmentioning
confidence: 99%
“…Although some recent trials have demonstrated that treatment with colchicine improved outcomes in patients with recent myocardial infarction, and chronic coronary disease, published evidence that treatment with colchicine may be associated with improvements in cardiovascular outcomes has been inconsistent. [20][21][22][23] In FAST, while prophylaxis against flares of gout was offered to all patients, only some accepted it, those who took it mainly did so at the very beginning of the trial, and it is likely that some patients chose to take it for less than the six months provided. It is unlikely that the relatively short-term administration of low dose colchicine or NSAIDs as prophylaxis, or any differences in concomitant use of colchicine or NSAIDs, even with the imbalances between treatment groups, had any major effect on the long-term outcomes of FAST.…”
Section: Discussionmentioning
confidence: 99%
“…One review included patients with ACS; however, only a narrative synthesis was conducted (8). Moreover, six reviews (5)(6)(7)(9)(10)(11) pooled data from patients with chronic coronary syndrome and ACS, despite the fact that these populations are clinically different. In contrast to our findings, four previous reviews (7)(8)(9)11) reported that colchicine was associated with an increased risk of gastrointestinal adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our findings, four previous reviews (7)(8)(9)11) reported that colchicine was associated with an increased risk of gastrointestinal adverse events. Only one review used the Hartung-Knapp adjustment for CIs (5). Besides, quality of evidence per outcome using GRADE methodology was evaluated in only one review (5).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations